Transformation of the activities of law enforcement entities in the economic sphere (part 2) - Grytsyshen, Dymytrii; Baranovska, Tatyana; Sergiienko, Larysa (Public Policy and Accounting, 2024)
The article examines various aspects of the organization and functions of law enforcement agencies of Ukraine, including their classification by purpose, areas of activity, and organizational and legal forms. Special attention is paid to the analysis of bodies that ensure the prevention and fight against criminal offenses in the economic sphere, such as the Security Service of Ukraine, the Bureau of Economic Security, the State Bureau of Investigation and the National Anti-Corruption Bureau. The article defines the types of law enforcement agencies according to their purpose (general, force, special), areas of activity (organizations of public order, state security, combating criminal offenses) and organizational and legal forms (agencies, bureaus, services, management). The role of these bodies in the system of law enforcement structures of Ukraine to ensure national security and effective management of law and order is defined. Criminal offenses investigated by the SBU and not related to state security were investigated, the specific weight of criminal offenses against the economic system in the structure of crimes investigated by this body was determined.